Biodegradable materials. Issue 5 (October 2017) - Godavitarne, Charles; Robertson, Alastair; Peters, Jonathan; Rogers, Benedict
Abstract: Biodegradable materials are a type of biomaterial. They are used to provide a specific application within the body and subsequently degrade over a given time. To function as a suitable biodegradable implant, degradation should occur once the purpose of the application has been achieved. Degradation is influenced by different variables, including the type of material used, its composition and the manufacturing process. Whilst much attention is now being focused on the development of such materials, the choice of bio-inert and biodegradable materials must be carefully considered before being used for a given application. Whilst biodegradable materials share similarities with their bio-inert counterparts, a number of advantages and disadvantages also exist. Numerous material types have been used for this purpose including polymers, metals and ceramics. This article aims to review the recent developments and advances of these materials, focusing on synthesis, degradation, advantages and disadvantages as well their potential clinical application. Future developments in this field will focus on augmenting mechanical strength whilst controlling degradation rate ultimately broadening their use and achieving enhanced clinical results.